The carbonate system of the northern South China Sea: Seasonality and exchange with the western North Pacific. (February 2021) - Roberts, Elliott G.; Dai, Minhan; Cao, Zhimian; Zhai, Weidong; Guo, Liguo; Shen, Samuel S.P.; Du, Chuanjun
Highlights: We show spatial and seasonal patterns of the carbonate system in the northern basin of the South China Sea (SCS) based, on a thus far, the largest dataset in a major world marginal sea. Exchange fluxes of the carbonate variables between the northern SCS and West Philippine Sea (WPS) via the Luzon Strait are constrained in the upper layer by Kuroshio intrusion and over the full depth range. We reveal significant spatial and seasonal changes in the carbonate chemistry of the deep SCS below 2000 db, attributable likely to spatial and seasonal variations in organic matter decomposition. Abstract: Using a most comprehensive, high quality, high-resolution dataset for any marginal sea up to depths >2000 db, we examined the seasonality of the carbonate system in the northern South China Sea (nSCS) and exchange with the West Philippine Sea (WPS) during 2009–2011. The carbonate system dynamics demonstrated evident spatial and seasonal variations. Winter exhibited the highest average surface dissolved inorganic carbon (DIC) concentrations (1936 ± 15 μmol kg −1 ), and summer had the lowest (1882 ± 12 μmol kg −1 ), primarily associated with more abundant freshwater inputs in summer. At 100 db depth, decreased DIC and total alkalinity (TA) values were observed within the Luzon Strait vicinity due to the influence of WPS waters. Higher DIC and TA concentrations were found within the central nSCS basin. The average Kuroshio contribution to the DIC inventory in the upper 150 db was seasonally significant, ranging between 11 and 32%, with the highest contributions during spring and winter. Below 2000 db, nSCS basin-averaged DIC was significantly higher than WPS-averaged DIC (∼23 µmol kg −1 difference) due to more organic matter decomposition in the nSCS basin. Within the basin, average deep water DIC values were highest in autumn, and averaged concentrations at >18.5°N were lower than at ≤18.5°N. Our datasets and analysis imply that (i) the significant seasonal and spatial patterns of carbonate chemistry in the nSCS are controlled by a combination of large-scale and smaller mesoscale physical processes; (ii) extrinsically from Asian monsoons via seasonal freshwater discharge and dynamic exchanges with open ocean waters; and (iii) intrinsically, through seasonal vertical mixing as well as mesoscale processes and their subsequent new productions. The seasonal and spatial variability in carbonate parameters established here serves as an essential baseline to monitor future changes to the nSCS and to compare with other marginal sea systems.